UJI FITOKIMIA DAN TOKSISITAS EKSTRAK ETANOL DAUN KAJAJAHI (Leucosyke capitellata (poir) Wedd.) - Nur Laila Zulfah Sari; Arif Nur Sho’im; Amanda Salwa Nur Azizah; Habel Ta’dung; Siti Nur Hadijah; Erwin (PROSIDING SEMINAR KIMIA, 2025)
Kajajahi Leaves (Leucosyke Capitellata (poir) Wedd.) or also called Kandih Uso which has benefits such as slowing attachment, aggregation and platelet secretion. Therefore, this study was carried out aimed at finding out the secondary metabolites of the Kajajahi leaf knowing and the toxicity of the Kajajahi leaf ethanol extract using the Brine Shrimp Lethality Test (BSLT) method. This extract is made by maceration using ethanol solvents for 7 days. Phytochemical tests are carried out to determine the secondary metabolites contained. Phytochemical content includes flavanoid, steroid, phenolic, saponin and quinone. The toxicity test was carried out using Artemia Salina L. shrimp larvae which was 48 hours old. The results of the extract toxicity are identified by the persentation of the death of the shrimp larvae using the LC50. This study shows the metabolites of secondary metabolites Ethanol extract Kajajahi leaf including flavanoid, steroid, phenolic, saponin and quinons and to be toxic with LC50 values of 0.0000166 ppm. Keywords: Brine Shrimp Lethality Test (BSLT), Kajajahi Leaves, Leucosyke Capitellata, Phytochemical Test, Toxicity